A Cross-Layer Location-Based Approach for Mobile-Controlled Connectivity. (12th December 2010) - Inzerilli, T.; Vegni, A. M.; Neri, A.; Cusani, R.
Abstract : We investigate into the potentiality of an enhanced Power and Location-based Vertical Handover (PLB-VHO) approach, based on a combination of physical parameters (i.e., location and power attenuation information), for mobile-controlled connectivity across UMTS and WLAN networks. We show that the location information in a multiparameter vertical handover can significantly enhance communication performance. In the presented approach a power attenuation map for the visited area is built and kept updated by exploiting the information sharing of power measurements with other cooperating mobile devices inside the visited networks. Such information is then used for connectivity switching in handover decisions. The analytical model for the proposed technique is first presented and then compared with a traditional Power-Based approach and a simplified Location-Based technique. Simulation results show the effectiveness of PLB-VHO approach, in terms of (i) network performance optimization and (ii) limitation of unnecessary handovers (i.e., mitigation of ping-pong effect ).